Impact of Decision-Making on Investment Performance: A Comprehensive Analysis (Journal of Asian Development Studies, 2023)
Investment decision-making is a complex and multifaceted process influenced by many factors, from individual cognitive biases to global economic conditions. This research explores the intricate interplay between decision-making and investment outcomes, delving into the key factors, styles, external influences, challenges, and best practices that shape the financial landscape. Utilizing a mixed-methods approach, combining quantitative analysis with qualitative insights from surveys, interviews, and case studies, the study aims to understand comprehensively how decisions impact investment performance. From the efficient market hypothesis to behavioural finance, the review synthesizes diverse perspectives, highlighting the psychological, behavioural, and cognitive dimensions of decision-making. Building on this foundation, the research identifies and analyzes the factors influencing investment decisions. From risk tolerance and behavioural biases to information asymmetry and decision-making styles, the study scrutinizes the intricacies that investors grapple with in their pursuit of sound financial choices. External factors, including economic conditions, regulatory changes, technological advancements, and geopolitical risks, are explored for their impact on decision-making processes. Challenges in decision-making, such as cognitive biases, adaptive strategy development, uncertainty management, and information overload, are identified and examined in depth. The research emphasizes the need for investors to navigate these challenges effectively to achieve long-term success.